Graphemes, traces and signing within the unimage of the contemporary city (2013)
The article raises the issue of interpreting the city emphasizing on the role of traces, graphemes and signing typical of contemporary urban conditions. According to the author, in the distinctive historical continuity of the organic trend it is possible to pin down the dynamics of medieval art, the baroque, Art Nouveau, cubism, German expressionism, Frank Lloyd Wright’s organicism and Jackson Pollock’s action painting, among others. Fractal forms found in nature are the result of chaotic dynamics in which biosystems work; they are the visual aspect of underlying natural laws. That is how water currents, winds, movements in plant life, seismic activity, heat waves, animal migrations and social human anatomy’s rhizomatous movements function. It is possible to square matter with energy in motion, the same as we can speak of quantum urban environments. Associated traces and fields entail it. Acts performed in the city can be seen in its radiography. It is in the flux, in the particle and its path, in the complex and entangled writing of the metacity in which the no-image (the unimage) of contemporary landscape is based on.